2022
DOI: 10.24925/turjaf.v10isp2.2966-2976.5646
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Extraction of Phenolic Compounds from Tomato Peel: Optimization of Extraction Conditions and Investigation of Phenolic Profile by LC-MS/MS

Abstract: With the increasing world population, the food need of humanity is increasing proportionally. Agricultural wastes constitute an important potential for the global economy as they contain components that are less preferred to be consumed as food due to their low bioavailability due to their indigestion in the human body or due to their sensory properties, but that may be beneficial to human health such as antioxidant substances and antimicrobial agents. The benefits of using these wastes in terms of economy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Kaempferol blocks the translation of viral proteins (Tsai et al, 2011). The p-coumaric acid was 429.99 ± 38.53 mg/100 g dry extract as the highest amount of acid in the tomato peel extract (Esmer et al, 2022). The presence of phenolic and the other bioactive compounds possibly explains the antioxidant potential found in all extracts.…”
Section: Extracted Yield and Total Phenolic Content In Different Samplesmentioning
confidence: 95%
See 1 more Smart Citation
“…Kaempferol blocks the translation of viral proteins (Tsai et al, 2011). The p-coumaric acid was 429.99 ± 38.53 mg/100 g dry extract as the highest amount of acid in the tomato peel extract (Esmer et al, 2022). The presence of phenolic and the other bioactive compounds possibly explains the antioxidant potential found in all extracts.…”
Section: Extracted Yield and Total Phenolic Content In Different Samplesmentioning
confidence: 95%
“…Nincevic-Grassino et al (2020), found that the phenolic content of tomato peels was 2626 and 2866 mg GAE /100 g which were extracted for 6 h with 96% and 70% hot ethanol, respectively. Also, Esmer et al (2022), reported that the total phenolic content of the tomato by product extract was 3819.32 mg GAE/100 g dry extract using extraction conditions at 100 °C for 5.26 h. These variations in total phenolic content may be caused by the plant variety, the environmental conditions, the harvest time fruit maturity and the method of analysis. 2), which showed the phenolic and the other bioactive compounds and their percentage of each ethanolic extract of the studied waste materials.…”
Section: Extracted Yield and Total Phenolic Content In Different Samplesmentioning
confidence: 99%
“…Alkali and alkali-assisted steam treatment to extract useful compounds from different plant biowastes are methods of choice in select situations to obtain value added products [40][41][42][43]. The treated substrates are compared with their respective controls by SEM to assess the level of polymeric destruction [44][45][46].…”
Section: Introductionmentioning
confidence: 99%